2013
DOI: 10.1002/bies.201200160
|View full text |Cite
|
Sign up to set email alerts
|

Late endosomal and lysosomal trafficking during integrin‐mediated cell migration and invasion

Abstract: Recently it has become clear that trafficking of integrins to late endosomes is key to the regulation of integrin expression and function during cell migration. Here we discuss the molecular machinery that dictates whether integrins are sorted to recycling endosomes or are targeted to late endosomes and lysosomes. Integrins and other receptors that are sorted to late endosomes are not necessarily degraded and, under certain circumstances, can be spared destruction and returned to the cell surface to drive cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 80 publications
(123 reference statements)
1
27
0
Order By: Relevance
“…Receptors are normally internalised into the endosomal/lysosomal compartment, when they can be either degraded or spared from degradation and returned to the cell surface [60].…”
Section: Resultsmentioning
confidence: 99%
“…Receptors are normally internalised into the endosomal/lysosomal compartment, when they can be either degraded or spared from degradation and returned to the cell surface [60].…”
Section: Resultsmentioning
confidence: 99%
“…ITGαv is over-expressed in human GC tissue and is associated with the five year survival rate of GC patients [28]. Additionally, studies have indicated that ITGαv affects lymph node metastasis and the formation of MMP-9, which could directly provide the driving force for cell migration, especially the migration of cancer cells through endocytosis exocytosis cycle [29, 30]. Combined with the down-regulation of ITGαv in our study, we speculate that this could lead to the decrease in invasion and metastasis of GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution made by Rab GTPases to acquisition of invasive behaviour has been intensively studied, and the molecular machinery that is responsible for trafficking receptors that control cell adhesion and cell migration is becoming well understood (Miller et al, 2000; Rainero and Norman, 2013). There is good evidence that Rab11 GTPase control of integrin and receptor tyrosine kinase (RTK) recycling drives invasive migration in cancer, and expression of Rab11 isoforms and their effectors, such as Rab-coupling protein (RCP), is linked to metastasis (Caswell et al, 2008).…”
Section: Introductionmentioning
confidence: 99%